Advances in Accounting Behavioral Research. - Karim, Khondkar E. (Advances in Accounting Behavioral Research Ser., 2018)
Focusing on research that examines individual and organizational behavior relative to accounting, this series promotes research across all areas of behavioral accounting, and encourages the development, discussion and expansion of theories from psychology, sociology and related disciplines to better understand accounting domains.